2019
DOI: 10.3390/coatings9050333
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Starch–Gellan Edible Coatings with Thyme Essential Oil for the Postharvest Preservation of Apple and Persimmon

Abstract: Starch–gellan (80:20) coating formulations were applied to apples and persimmons to analyse their effectiveness controlling the weight loss, respiration rate, fruit firmness, and fungal decay during postharvest. Thyme essential oil (EO) was incorporated (0.25 and 0.5 g per g of polymer) directly or encapsulated in lecithin to enhance antifungal action. Coatings did not reduce weight loss or firmness changes in apples, but they prevented water loss in persimmons. In contrast, no significant effect of the coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 49 publications
7
43
0
Order By: Relevance
“…However, it was noted that the RQ was higher for coated papaya as compared to control papaya. This suggested that the transition of metabolic substrates from carbohydrates to organic acids was higher in coated papaya, which was in agreement with the findings of Sapper et al [ 42 ] and Fagundes et al [ 44 ]. The authors found that an RQ equal to 1 signifies that the metabolic substrates are carbohydrates, while an RQ higher than 1 signifies that the metabolic substrates are organic acids.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, it was noted that the RQ was higher for coated papaya as compared to control papaya. This suggested that the transition of metabolic substrates from carbohydrates to organic acids was higher in coated papaya, which was in agreement with the findings of Sapper et al [ 42 ] and Fagundes et al [ 44 ]. The authors found that an RQ equal to 1 signifies that the metabolic substrates are carbohydrates, while an RQ higher than 1 signifies that the metabolic substrates are organic acids.…”
Section: Resultssupporting
confidence: 92%
“…Additionally, Sapper et al [ 42 ] described that the RQ was influenced by changes in respiration rate, indicating the existence of the substrate used during the respiration process of fruit. The RQ was relying on both O 2 and CO 2 production rates, resulting in a decrease in O 2 and an increase in CO 2 [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Edible films and coatings often containing bioactive agents or food additives like nutrients are gaining relevance as potential tools to reduce the deleterious effects of the incidence of microorganisms or to improve the nutritional value of a product [8]. In the research by Sapper et al [9], polysaccharide protein films with the addition of thyme essential oil were obtained, which has a strong in vitro fungicidal effect. However, in vivo studies did not confirm the inhibitory effect on the surface of apples.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, a very active research field is the replacement of commercial citrus waxes, which 61 are often a vehicle for the application of synthetic fungicides, for natural edible coatings (ECs) with antifungal properties (Valencia-Chamorro et al, 2011b). The antifungal activity of such ECs is mainly accomplished through the incorporation to the formulations of non-polluting antifungal ingredients such as plant extracts (Nair et al, 2018), essential oils (Sapper et al, 2019), food additives or low toxicity compounds classified as generally recognized as safe (GRAS) (Guimarães et al, 2019), and microbial antagonists as biocontrol agents (Marín et al, 2017). Among them, GRAS salts show some important advantages such as their high solubility in water, easy availability, and relatively low cost (Palou, 2018).…”
mentioning
confidence: 99%
“…On the other hand, starch-based coatings are suitable for gaining new functionalities through the incorporation into the formulations of additional ingredients. For example, starch ECs formulated with active antifungal ingredients such as essential oils (Sapper et al, 2019), natamycin-cyclodextrin complex (Yang et al, 2019), lactic acid bacteria (Marín et al, 2019), and GRAS salts like potassium sorbate (Mehyar et al, 2011) have significantly controlled postharvest decay of guava, apple, persimmon, banana, cherry tomato, grapes, and cucumber, among others.…”
mentioning
confidence: 99%